Reoperation as a Result of Raised Intracranial Pressure Associated with Cyst Formation in Tumor Cavity after Intracranial Tumor Resection: A Report of Two Cases - Jinlu Yu; Wenji Xiong; Limei Qu; Haiyan Huang (Case Reports in Medicine)
Reoperation as a result of increased intracranial pressure (ICP) associated with cyst formation in an intracranial tumor resection cavity is a rare clinical condition. We report two cases of reoperation as a result of raised ICP associated with cyst formation in the tumor resection cavity, one arising after glioma resection and the other after meningioma resection. In both cases, a “valve”-like structure was noted intraoperatively in the roof region of the tumor resection cavity. Surgical resection of the “valve”-like structure led to slow regression over several months after the reoperation rather than to immediate disappearance of the cyst. Both cases illustrate that the “valve”-like structure formed in the roof region of the tumor resection cavity may be responsible for cyst formation. Surgical resection of it provides good long-term outcomes in such patients though short-term outcomes are unsatisfactory; we speculate that if the resection of the cortical tissue around the “valve”-like structure is enough wide, its return may be avoided.